Analisis Kerjasama Antara Publisher Dengan Google Adsense Dalam Perspektif Hukum Ekonomi Syariah - Hoerusolihin; Ahmad Bisri Musthafa (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2022)
In this 21st century, humans are faced with various kinds of social media as a means of providing information and communication between humans. The purpose of this study is to analyze the collaboration between publishers and google adsense in the perspective of sharia economic law. The research method used is descriptive qualitative. The results show First, the implementation of cooperation between publishers and Google Adsense in the PPC program begins with the publisher registering a blog or website to Google, then Google filters and verifies the publisher's blog which will then be entered in advertisements as a form of cooperation between the two, which is then after the website or the site already has an ad, then the ad can be clicked on by the user (visitor) which will later become an advantage for the publisher and google adsense. Second, referring to the implementation of cooperation between publishers and Google Adsense which has been described in point one, that this collaboration in Islam is known as cooperation in the form of syirkah abdan. In this case, there is a contract or cooperation agreement to carry out an advertising business and the results are divided into two according to the agreement.